2017
DOI: 10.1242/jeb.145235
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of increased yolk testosterone content on development and oxidative status in gull embryos

Abstract: Hormone-mediated maternal effects generate variation in offspring phenotype. In birds, maternal egg testosterone (T) exerts differential effects on offspring traits after hatching, suggesting that mothers experience a trade-off between contrasting T effects. However, there is very little information on T pre-natal effects. In the yellow-legged gull (Larus michahellis), we increased yolk T concentration within physiological limits and measured the effects on development and oxidative status of late-stage embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 97 publications
(122 reference statements)
2
11
1
Order By: Relevance
“…Finally, we observed that males had significantly larger brains than females after controlling for embryo size or mass. A sex difference in brain mass is consistent with evidence from previous studies (Parolini et al, 2017c), although it was not affected by yolk supplementation with vitamin E, corticosterone or their mixture.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, we observed that males had significantly larger brains than females after controlling for embryo size or mass. A sex difference in brain mass is consistent with evidence from previous studies (Parolini et al, 2017c), although it was not affected by yolk supplementation with vitamin E, corticosterone or their mixture.…”
Section: Discussionsupporting
confidence: 91%
“…condition of the female 39 ), age of the female 62 , predators 63 , 64 and parasites 65 . Within the female, physiological processes like stress hormone 63 , yolk steroid 66 , testosterone 67 and carotenoid production 68 , as well as trade-offs with other traits like lateral plate production 60 and immune response 69 can also lead to variation in features of eggs and clutches. For the marine stickleback population studied here, little is known about habitat variability in the open sea where they overwinter and where the early stages of ova maturation begin 60 , but adults aggregate into small tidal channels and salt marsh pools for spawning starting in late spring (just prior to the last phases of egg maturation) where the habitat conditions (biotic and abiotic) are similar for all females (Shama, pers.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, since maternal effects can occur through variation in egg mass, macroconstituents (e.g. albumen content) and quantitatively minor components that may affect post-natal performance (Blount et al 2002, Christians 2002, Bonisoli-Alquati et al 2007, Groothuis and Schwabl 2008, Navara and Mendonça 2008, Parolini et al 2017a), we analysed the relationship between eggshell pigmentation and egg mass, yolk/albumen ratio, yolk total antioxidant capacity (TAC) and yolk testosterone concentration. Fourth, we tested whether eggshell pigmentation pattern was related to female quality-related traits.…”
Section: Introductionmentioning
confidence: 99%